PENGARUH EXCESS CASH DAN INSUFFICIENT CASH TERHADAP KINERJA PERUSAHAAN DAN REAKSI PASAR (STUDI PADA PERUSAHAAN YANG TERDAFTAR DI BEI TAHUN 2010-2013) - Merri Dwi Nurrani; Evita Puspitasari; Rolland E. Fanggidae (JAF (Journal of Accounting and Finance), 2019)
The objects of this research were nonfinancial companies registered on Indonesian Stock Exchange with samples of 79 companies on 2010-2013 (including time lag). Data was analyzed usingPooled Least Square regression with Eviews software as the tool. Using 5% significancy level, this research implied that (1) excess cash had positive significant influence on firm performance, (2) insufficient cash had positive but no significant influence on firm performance, (3) excess cash had negative but no significant influence on market reaction, and (4) insufficient cash had negative significant influence on market reaction. These results implied that the market responded to insufficient cash more than excess cash in the companies and firm performance would be increasing because of excess cash due to the decrease of external financing cost.